Molecular characterization and phylogenetic analyses of MetAP2 gene and protein of Nosema bombycis isolated from Guangdong, China - Qazi, Izhar Hyder; Yuan, Ting; Yang, Sijia; Angel, Christiana; Liu, Jiping (Frontiers in Veterinary Science, 2024)
Background: Pebrine, caused by microsporidium Nosema bombycis, is a devastating disease that causes serious economic damages to the industry. Studies on development of therapeutic and diagnostic options for managing pebrine in silkworms are very limited. Methionine aminopeptidase type 2 (MetAP2) of microsporidia is an essential gene for their survival and has been exploited as the cellular target of drugs such as fumagillin and its analogues in other host species, including honeybees. Methods: In the present study, using molecular and bioinformatics tools, we performed in-depth characterization and phylogenetic analyses of MetAP2 of Nosema bombycis isolated from Guangdong province of China. Results: The full length of MetAP2 gene sequence of Nosema bombycis (Guangdong isolate) was found to be1278 base pairs (bp), including an open reading frame of 1077 bp, encoding a total of 358 amino acids. The bioinformatics analyses predicted the presence of typical alpha-helix structural elements, and absence of transmembrane domains and signal peptides. Additionally, other characteristics of a stable protein were also predicted. The homology-based 3D models of MetAP2 of Nosema bombycis (Guangdong isolate) with high accuracy and reliability were developed. The MetAP2 protein was expressed and purified. The observed molecular weight of MetAP2 protein was found to be ~43-45 kDa. The phylogenetic analyses showed that MetAP2 gene and amino acids sequences of Nosema bombycis (Guangdong isolate) shared a close evolutionary relationship with Nosema spp. of wild silkworms, but it was divergent from microsporidian spp. of other insects, Aspergillus spp., Saccharomyces cerevisiae, and higher animals including humans. These analyses indicated that the conservation and evolutionary relationships of MetAP2 are closely linked to the species relationships. Conclusion: This study provides solid foundational information that could be helpful in optimization and development of diagnostic and treatment options for managing the threat of Nosema bombycis infection in sericulture industry of China.